2020
DOI: 10.3389/fgene.2020.00213
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study Reveals Novel Marker-Trait Associations (MTAs) Governing the Localization of Fe and Zn in the Rice Grain

Abstract: Micronutrient malnutrition due to Fe and Zn, affects around two billion people globally particularly in the developing countries. More than 90% of the Asian population is dependent on rice-based diets, which is low in these micronutrients. In the present study, a set of 192 Indian rice germplasm accessions, grown at two locations, were evaluated for Fe and Zn in brown rice (BR) and milled rice (MR). A significant variation was observed in the rice germplasm for these micronutrients. The grain Fe concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
54
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 71 publications
5
54
1
Order By: Relevance
“…Therefore, pooled grain Fe and Zn data of two years is more reliable than single-year data. Significant genetic variation was observed among 56 fine and coarse grain accessions for Fe and Zn contents in brown rice (Figure 1A), which is in accordance with recent reports [13,36]. The Fe and Zn contents in unpolished grains of fine/aromatic rice accessions were relatively higher than coarse grain accessions (Figure 1B).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Therefore, pooled grain Fe and Zn data of two years is more reliable than single-year data. Significant genetic variation was observed among 56 fine and coarse grain accessions for Fe and Zn contents in brown rice (Figure 1A), which is in accordance with recent reports [13,36]. The Fe and Zn contents in unpolished grains of fine/aromatic rice accessions were relatively higher than coarse grain accessions (Figure 1B).…”
Section: Discussionsupporting
confidence: 90%
“…Significant positive correlation was present between Fe and Zn contents (Figure 1C). Several other studies have also reported a positive association between these two mineral contents [10,36,45,46]. Overall, these results indicate the prevalence of wide genetic variability in studied rice accessions for grain Fe and Zn contents and possibility of their simultaneous improvement.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…During recent years, SSR markers based genotyping has proven to be very useful for exploring a variety of surreptitious information in plants, ranging from domestication traits to crop improvement through marker-assisted breeding [37][38][39][40]. Although, individual reports on micronutrient density and SSR based genetic diversity in rice have been recently published [10,12,13,36,41], however, to date, a combined study of grain Fe and Zn contents and trait linked SSR markers based genetic diversity is obscure. In this study, we assessed genetic diversity in the representative subset of a large collection of local and exotic rice germplasm for grain Fe and Zn contents using trait linked SSR markers.…”
Section: Discussionmentioning
confidence: 99%